The COVID-19 Pandemic: Identifying Adaptive Solutions for Colorectal Cancer Screening in Underserved Communities. (11th August 2020) - Nodora, Jesse N; Gupta, Samir; Howard, Nicole; Motadel, Kelly; Propst, Tobe; Rodriguez, Javier; Schultz, James; Velasquez, Sharon; Castañeda, Sheila F; Rabin, Borsika; Martínez, María Elena
Abstract: The 2019 novel coronavirus disease (COVID-19) pandemic has dramatically impacted numerous health and economic fronts. Because of the stay-at-home mandate and practice of physical distancing, nearly all preventive care measures have been halted, including colorectal cancer (CRC) screening. The health consequences of this temporary suspension are of great concern, particularly for underserved populations, who experience substantial CRC-related disparities. In this commentary, we describe challenges and opportunities to deliver COVID-19–adapted CRC screening to medically underserved populations receiving care in community health centers (CHC). This perspective is based on key informant interviews with CHC medical directors, teleconference discussions, and strategic planning assessments. To address the unprecedented challenges created by the COVID-19 pandemic, we identify 2 broad calls to action: invest in CHCs now and support equitable and adaptable telehealth solutions now and in the future. We also recommend 4 CRC-specific calls to action: establish COVID-19–adapted best practices to implement mailed fecal immunochemical test programs, implement grassroots advocacy to identify community gastroenterologists who commit to performing colonoscopies for CHC patients, assess cancer prevention priorities among individuals in underserved communities, and assess regional CRC screening and follow-up barriers and solutions. The COVID-19 pandemic may further exacerbate existing CRC screening disparities in underserved individuals. This will likely lead to delayed diagnosis, a shift to later-stage disease, and increased CRC deaths. To prevent this from happening, we call for timely action and a commitment to address the current extraordinary CRC screening challenges for vulnerable populations.